Peran Branding dan Desain dalam Usaha Pencitraan Identitas Bangsa - Suhardjono, Liliek Adelina (Humaniora, 2015)
This research examined the role of branding and design in the process of city/nation identity creation. Recently, there are a growing phenomenon of branding within cities and/or nations. The growing competition between cities to increase the number of visitors and investors, foreign and domestics, and develop new businesses which in turn could absorb talents and manpowers was the background for the phenomenon. With the development of branding awareness, more and more cities/nations commit to a branding strategy so that they can measure the journey of their city/nation branding. This article began with a number of basic definitions about the city/nation branding concept; and then was followed by the case studies. The sources for this paper are derived from books and journals, the author’s travelling experiences, and articles from the internet regarding the city branding and city tourism.